Relationship of Knowledge and Attitude to the Role of Health Personnel in Management of Stunting Events in School Children, Tuah Negeri District, Musi Rawas Regency - Nirwana Nirwana; Rico Januar Sitorus; Nur Alam Fajar (Budapest International Research and Critics University, 2021)
Prevention of stunting is carried out by health service providers in an effort to create the next generation of the nation that is healthy, reactive and productive. The purpose of this study was to see the relationship between knowledge and attitudes with the role of health workers in dealing with stunting in school children. Method : Quantitative research with cross sectional design. The population is 156. Sample The study was conducted on 55 respondents who met the inclusion criteria. The measuring instrument in this study is a questionnaire sheet with data analysis using Univariate, Bivariate, and Multivariate tests. The research was conducted in March 2021 in the working area of the Air Beliti Health Center. Result: there is a significant relationship between attitudes and the role of health workers in preventing stunting in school children (p = 0.043), and there is no relationship between knowledge and the role of health workers and the role of health workers in dealing with stunting (p = 0.446). The results of the multivariate analysis using the logistic regression method showed an effect of 5.925 times on the role of health workers in dealing with stunting. Conclusion: from the results of the study, it was found that there was a relationship between attitude and the role of health workers in dealing with stunting in school children, it was suggested to health workers to improve good attitudes as a control effort by developing programs with more interesting innovations and teaching posyandu cadres. So that cadre mothers can convey and inform those who are pregnant, and have pre-school and elementary school age children so that the incidence of stunting can be reduced